THE BRONZE AGE PRESTIGE AXE FROM VINŢU DE JOS - Cristian Ioan Popa (Journal of Ancient History and Archaeology, 2019)
In 1996, the research team in the archaeological site from Vințu de Jos-Deasupra Satului was presented with an ornate sandstone axe that had been found by accident. The item was whole, naviforme, approximately centrally perforated and its sides had rich spiralling incised decorations. Another, more rudimentary decoration that was probably made subsequently is still visible on its upper part. It is most likely an imported item, possibly from the south-Danube or Aegean region, used by its owner as a prestige good. The axe is a unique item for the current Romanian space and it must have belonged to the Wietenberg II Bronze Age settlement that was documented both as a rich settlement and as a necropolis which was located in its vicinity.